Circular economy in Germany: A methodology to assess the circular economy performance of NUTS3 regions - Mirko Kruse; Jan Wedemeier (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2022)
There is currently a massive methodological gap in the spatial analysis of the Circular Economy (CE) performance in general and in Germany particularly. The authors present a methodology to assess this performance in German regions. The methodology consists of 26 indicators in seven dimensions, namely Policy, Innovation, Circular Employment, Consumption and Production, Waste Management, Socio-economic Development, Municipal Sustainability. Data was obtained from different sources and focuses on the base year 2018. The analysis reveals that Germany does not show a clear core-periphery pattern when it comes to regional CE performance. Instead, the pattern is more differentiated with both urban and rural regions of different sizes being able to rank high in CE performance.
Keywords: O18; P48; R1; R11; 330; Circular Economy; Germany; Regional Assessment; Sustainability; NUTS3